The discovery of Noah's Ark - Griffin, G. Edward ([Westlake Village, Calif.] : American Media, 1993)
The video features expert testimony and evidences of the discovery of Noah's ark on Mount Ararat in Turkey
Narrated by G. Edward Griffin
Keywords: Noah's Ark; Deluge; Ararat, Mount (Turkey)